l log1000

Evaluate the following logarithmic expression

log1000

Evaluate log1000

You didn't enter a base

We'll do bases e and 2-10

Evaluate loge(1000) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = e and x = 1000, we have:

loge(1000)  =  Ln(1000)
  Ln(e)

Ln(e) = 1

loge(1000) = 6.9077552789821

Evaluate log2(1000) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 2 and x = 1000, we have:

log2(1000)  =  Ln(1000)
  Ln(2)

log2(1000) = 9.9657842846621

Evaluate log3(1000) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 3 and x = 1000, we have:

log3(1000)  =  Ln(1000)
  Ln(3)

log3(1000) = 6.2877098228682

Evaluate log4(1000) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 4 and x = 1000, we have:

log4(1000)  =  Ln(1000)
  Ln(4)

log4(1000) = 4.982892142331

Evaluate log5(1000) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 5 and x = 1000, we have:

log5(1000)  =  Ln(1000)
  Ln(5)

log5(1000) = 4.2920296742202

Evaluate log6(1000) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 6 and x = 1000, we have:

log6(1000)  =  Ln(1000)
  Ln(6)

log6(1000) = 3.8552916268154

Evaluate log7(1000) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 7 and x = 1000, we have:

log7(1000)  =  Ln(1000)
  Ln(7)

log7(1000) = 3.5498839873648

Evaluate log8(1000) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 8 and x = 1000, we have:

log8(1000)  =  Ln(1000)
  Ln(8)

log8(1000) = 3.3219280948874

Evaluate log9(1000) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 9 and x = 1000, we have:

log9(1000)  =  Ln(1000)
  Ln(9)

log9(1000) = 3.1438549114341

Evaluate log10(1000) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 10 and x = 1000, we have:

log10(1000)  =  Ln(1000)
  Ln(10)

log10(1000) = 3

Final Answer


loge(1000) = 6.9077552789821
log2(1000) = 9.9657842846621
log3(1000) = 6.2877098228682
log4(1000) = 4.982892142331
log5(1000) = 4.2920296742202
log6(1000) = 3.8552916268154
log7(1000) = 3.5498839873648
log8(1000) = 3.3219280948874
log9(1000) = 3.1438549114341
log10(1000) = 3